1993
DOI: 10.1006/pmed.1993.1064
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Prevention: The Case for Carotenoids and Anti-Oxidant Nutrients

Abstract: The most convincing evidence for a preventive role for any modality is obviously demonstration of incidence reduction produced by that modality. However, cancer prevention trials with cancer incidence as an endpoint have logistic problems rendering them essentially impossible to conduct for most malignancies. Hence a workable strategy often involves analysis of other, indirect lines of evidence to reach conclusions. For oral cancer, dietary epidemiologic evidence points to a protective role for foods rich in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Beta-carotene has been said to be efficacious against oral leukoplakia in previous studies, 30 although the reported outcomes are diverse; the overall response rates range from 27.5 to 73% [31][32][33][34][35][36] and none had adopted CONSORT guidelines. Table 4 shows the summary of RCTs that reported on systematic chemoprevention trials using retinoids and carotenoids for the treatment of oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-carotene has been said to be efficacious against oral leukoplakia in previous studies, 30 although the reported outcomes are diverse; the overall response rates range from 27.5 to 73% [31][32][33][34][35][36] and none had adopted CONSORT guidelines. Table 4 shows the summary of RCTs that reported on systematic chemoprevention trials using retinoids and carotenoids for the treatment of oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found reductions in oral leukoplakia using beta-carotene, especially when combined with retinol, in subjects using tobacco or alcohol (Garewal et al, 1993). However lung cancer rates were slightly higher in Finnish smokers given betacarotene (Alpha-tocopherol Beta-carotene Prevention Study Group, 1994) but overall cancer incidence and death rates were not raised in groups containing fewer smokers (Greenberg et al, 1996;Hennekens et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids and flavonoids, due to their antioxidant properties and nutritional benefits, have been some of the most studied dietary and therapeutic components in the dietetics and preventive medicine areas, yielding hundreds of publications and reviews [36,39,41,65,66,[122][123][124][125][126]. Much anecdotal or scientific evidence indicate that some of these components may possess potent antioxidant, anti-inflammatory, antiallergic, hypolipidaemic, vasoprotective, and anticarcinogenic properties [127] and protect against oxidative stress, coronary heart diseases, certain cancers, and other age-related diseases.…”
Section: Dietetics Of Citrus Fruits Pigmentsmentioning
confidence: 99%